2022
DOI: 10.3892/etm.2022.11592
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis identification of AKT3 and RAC1 as key genes in postmenopausal osteoporosis

Abstract: Postmenopausal osteoporosis (PMO) is an aging-associated disease that manifests as degradation of bone tissue microstructure leading to decreased bone mass and increased bone fragility. Differentiation of peripheral blood mononuclear cells into osteoclasts is an important process in the development of PMO and identification of key genes that drive differentiation is essential to reveal the mechanism of PMO. The present study combined bioinformatics analysis of a Gene Expression Omnibus dataset of PMO and drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…The zebrafish rac1 gene, also known as rac1a , belongs to the Rac family of small GTPases and plays a vital role in a variety of cellular processes, including cytoskeletal assembly ( Ding et al, 2022 ), cell development ( Tejada-Simon, 2015 ), DNA damage reparation ( Fritz & Henninger, 2015 ), cell motility, and migration ( Chan et al, 2005 ), and has thus become an attractive anti-tumor target ( Bailly et al, 2022 ; Ma et al, 2023 ). During osteoclast differentiation, Rac1 is highly up-regulated ( Zhang et al, 2022 ; Zhou et al, 2020 ) and thought to be involved in mediating the inhibition of osteoclast differentiation ( Guo et al, 2021 ), although other studies have reported different results ( Li et al, 2023a ). Rac1 is also necessary for normal osteogenic function and bone mineral density maintenance ( Huck et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish rac1 gene, also known as rac1a , belongs to the Rac family of small GTPases and plays a vital role in a variety of cellular processes, including cytoskeletal assembly ( Ding et al, 2022 ), cell development ( Tejada-Simon, 2015 ), DNA damage reparation ( Fritz & Henninger, 2015 ), cell motility, and migration ( Chan et al, 2005 ), and has thus become an attractive anti-tumor target ( Bailly et al, 2022 ; Ma et al, 2023 ). During osteoclast differentiation, Rac1 is highly up-regulated ( Zhang et al, 2022 ; Zhou et al, 2020 ) and thought to be involved in mediating the inhibition of osteoclast differentiation ( Guo et al, 2021 ), although other studies have reported different results ( Li et al, 2023a ). Rac1 is also necessary for normal osteogenic function and bone mineral density maintenance ( Huck et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a small GTPase, RAC1 (Ras-related C3 botulinum toxin substrate 1) is upregulated to activate disulfidptosis [ 10 ]. During osteoclast differentiation, RAC1 undergoes significant upregulation; its knockdown suppresses osteoclast differentiation and monocyte apoptosis [ 34 ]. PRDX1 (peroxiredoxin 1) is a known modulator of reactive oxygen species that regulates oxidative stress and BMP signalling-driven osteogenesis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACTN1 (Alpha-Actinin-1) encodes a non-muscle cytoskeletal protein that binds actin to the cell membrane [ 54 ]. Genetic variants and differential expression of the ACTN1 have been reported in various diseases, including congenital macrothrombocytopenia, Angelman syndrome, Bowen disease, postmenopausal osteoporosis, lupus erythematosus, and COVID-19 [ 54 57 , 69 , 70 ]. There is evidence that cannabinoids can attenuate seizures and EEG abnormalities in Angelman syndrome [ 71 , 72 ], effective in treating individuals with osteoporosis [ 73 ], reduce cell proliferation and induce apoptosis in melanoma cells [ 74 ], as well as downregulate the immune response in lupus erythematosus [ 75 ].…”
Section: Discussionmentioning
confidence: 99%